Evaluation of the anti-cancer potential of Cedrus deodara total lignans by inducing apoptosis of A549 cells - Xiaofeng Shi; Ruiqin Du; Junmin Zhang; Yanping Lei; Hongyun Guo (BMC, 2019)
Abstract Background Cedrus deodara (Roxb.) Loud (normally called as deodar), one out of four species in the genus Cedrus, exhibits widely biological activities. The Cedrus deodara total lignans from the pine needles (CTL) were extracted. The aim of the study was to investigate the anticancer potential of the CTL on A549 cell line. Methods We extracted the CTL by ethanol and assessed the cytotoxicity by CCK-8 method. Cell cycle and apoptosis were detected by a FACS Verse Calibur flow cytometry. Results The CTL were extracted by means of ethanol hot refluxing and the content of total lignans in CTL was about 55.77%. By the CCK-8 assays, CTL inhibited the growth of A549 cells in a dose-dependent fashion, with the IC50 values of 39.82 ± 1.74 μg/mL. CTL also inhibited the growth to a less extent in HeLa, HepG2, MKN28 and HT-29 cells. Conclusion At low doses, the CTL effectively inhibited the growth of A549 cells. By comparison of IC50 values, we found that A549 cells might be more sensitive to the treatment with CTL. In addition, CTL were also able to increase the population of A549 cells in G2/M phase and the percentage of apoptotic A549 cells. CTL may have therapeutic potential in lung adenocarcinoma cancer by regulating cell cycle and apoptosis.